Key success factors analysis for improving cost performance of green retrofit infrastructure on the jetty project - Ato Muhan Iswidyantara; Albert Eddy Husin (Universitas Mercu Buana, 2023)
Several rating definitions must be met following the envision's system. The envisioned system aims to develop the green building concept in the existing jetty building. These definitions are quality of life, leadership, resource allocation, nature, climate, and resilience. This sustainability is needed to initiate changes in the planning, design, and provision of sustainable infrastructure together with the company. This also applies to implementing long-term infrastructure investments that are more cost-effective, resource-efficient, and adaptable. The study uses a qualitative and quantitative method, where data is obtained by distributing questionnaires and simulating using Statistical Products and Solution Services (SPSS). The application of Value Engineering (VE) and Life Cycle Cost Analysis (LCCA) has been chosen by researchers on existing jetty buildings with the green jetty concept, with investment costs in economic green jetty buildings and a return on investment costs of less than four years. In achieving the ten most influential factors in improving cost performance in sustainable dock construction, the results of the SPSS simulation processing obtained the ten most influential factors, namely: Planning, Energy, Siting, Materials, Ecology, Community, Economy, Operation, and Maintenance Cost, Follow-up Inspection, and Labor Experience.